Pentingnya Pengetahuan Perawatan Lensa Kontak Lunak Bagi Pemakai Di Optik Citra Padang - ., Ihsan Saunir (CV. ITTC INDONESIA, 2023)
This scientific paper discusses the importance of soft contact lens care knowledge for users in Padang Citra Optics. This study aims to determine: Knowledge, care for users, the use , the impact of wearing and maintaining soft contact and also handling of the use and maintenance of soft contact lenses at Optik Citra Padang. This research design uses descriptive quantitative method. The population in this study was all patients wearing soft contact lenses at Optik Citra Padang in the period 15 July 2021-15 August 2021. Data were collected through questionnaires and research instruments using a Check List. The results showed that the respondents did not fully know the proper and correct care of soft contact lenses, this was seen as many as 24 respondents (53%) knew the correct soft contact lens care procedure and as many as 21 respondents (47%) did not know the treatment procedures. correct soft contact lenses, 21 respondents (47%) understand how to properly put on and remove soft contact lenses and 24 respondents (53%) do not understand how to properly install soft contact lenses, 20 respondents (44.40%) know about the impact of wearing and maintaining soft contact lenses that are not up to standard and as many as 25 respondents (55.60) do not know about the impact of wearing and maintaining soft contact lenses that are not up to standard, 14 respondents (31%) know how to handle the use and care of soft contact lenses and 31 respondents (69%) do not know how to handle from wearing soft contact lenses. There are several suggestionsFor RO to provide information to, For opticians, it is recommended to improve the quality of eye health services to the public, for academies, it is recommended to improve the quality of education. (4) For the public, it is recommended that when wearing and caring for contact lenses, more attention should be paid to use and care for them properly so as not to cause an impact on eye health.